Pengaruh Antara Service Innovativeness Terhadap Relative Attractiveness Yang Dimediasi Oleh Imposed Service Innovation - Pradana, Dennis; Vandayuli Riorini, Sri (Fakultas Ekonomi Universitas Gresik, 2023)
COVID-19 primarily spreads through close contact between humans and has affected retailing industries extremely hard. To manage the situation retailers have turned to service innovation to change their operations to make consumers feel safe while shopping. This research focuses on the role of service innovativeness in retailing firms during the COVID-19 pandemic through an empirical study of almost 6000 consumers of 28 retailing firms. The results suggested that retailers with high service innovativeness performed COVID-19 imposed innovations better to improve their relative attractiveness. For retailers with physical stores, changes to the servicescape and the offering were found to be the key antecedents of service innovativeness. The findings on COVID-19 imposed service innovations demonstrate the importance of service innovativeness in successfully changing retailing services to adjust to the restrictions from governments and safety needs of customers